(2x+3)/(4x+5)=(5x+2)/(10x+2)
tìm x
Tìm x,y
a) x/2=y/3 và xy+=24
b) 4x+5/10x+2=2x+3/5x+2
a)x/2=y/3
=>x.3=y.2
x.3/2=y
x.1,5=y
=>y gấp 1,5 lần x
x=24:(1+1,5)
x=9,6
y =24-9,6=14,4
I : Tìm x , y
a) x^2+y^2-2x+4y+5=0
b) 4x^2+y^2-4x-6x+10=0
c) 5x^2-4xy+y^2-4x+4=0
d)2x^2-4xy+4y^2-10x+25=0
help me
a. Ta có: x2+y2-2x+4y+5=0
⇌(x-1)2+(y-2)2=0
\(\Leftrightarrow\left\{{}\begin{matrix}x-1=0\\y-2=0\end{matrix}\right.\)\(\Leftrightarrow\left\{{}\begin{matrix}x=1\\y=2\end{matrix}\right.\)
b. Ta có: 4x2+y2-4x-6y+10=0
⇌ (2x-1)2+(y-3)2=0
\(\Leftrightarrow\left\{{}\begin{matrix}2x-1=0\\y-3=0\end{matrix}\right.\)\(\Leftrightarrow\left\{{}\begin{matrix}x=\dfrac{1}{2}\\y=3\end{matrix}\right.\)
c.Ta có: 5x2-4xy+y2-4x+4=0
⇌(2x-y)2+(x-2)2=0
\(\Leftrightarrow\left\{{}\begin{matrix}2x-y=0\\x-2=0\end{matrix}\right.\)\(\Leftrightarrow\left\{{}\begin{matrix}y=4\\x=2\end{matrix}\right.\)
d.Ta có: 2x2-4xy+4y2-10x+25=0
⇌ (x-2y)2+(x-5)2=0
\(\Leftrightarrow\left\{{}\begin{matrix}x-2y=0\\x-5=0\end{matrix}\right.\)\(\Leftrightarrow\left\{{}\begin{matrix}y=\dfrac{5}{2}\\x=5\end{matrix}\right.\)
1)6x-8=3x+1
2)12-10x=25-30x
3)3(2x+3)-2(4x-5)=10x+21
4)5(5x-3)-3(2x-4)11-5x
5)4(2-3x)-5(1-2x)=4-6x
6)8(4x-3)-3(2-3x)=13-40x
7)10x-5(1-4x)=5x-11
8)-3(3-4x)-5(4-3x)=12x-50
9)-2(20x-3)-3(4x-5)=9-2(2x-3)
10)-5(2-3x)+3(5-2x)=3x+3(3-5x)
1)6x-8=3x+1
6x-3x=1+8
3x=9
x=3
Vậy x=3
2: 12-10x=25-30x
=>20x=13
=>x=13/20
3: \(3\left(2x+3\right)-2\left(4x-5\right)=10x+21\)
=>6x+9-8x+10=10x+21
=>10x+21=-2x+19
=>12x=-2
=>x=-1/6
4: \(\Leftrightarrow25x-15-6x+12=11-5x\)
=>19x-3=11-5x
=>24x=14
=>x=7/12
5: \(\Leftrightarrow8-12x-5+10x=4-6x\)
=>4-6x=-2x+3
=>-4x=-1
=>x=1/4
6: \(\Leftrightarrow32x-24-6+9x=13-40x\)
=>41x-30=13-40x
=>81x=43
=>x=43/81
7: \(\Leftrightarrow10x-5+20x=5x-11\)
=>30x-5=5x-11
=>25x=-6
=>x=-6/25
bài 2
2x^2(4x-5x^3)+10x^5 -5x^3
(x-2)(x^2-2x+4)+(x-4)(x+2)
a: \(=8x^3-10x^5+10x^5-5x^3=3x^3\)
b: \(=x^3-2x^2+4x-2x^2+4x-8+x^2+2x-4x-8\)
\(=x^3-3x^2+4x-16\)
BT1: Tìm x biết.
a, (5x-1)(2x+7)-(x+1)(6x-5)=16
b, (10x+9).x-(5x-1).(2x+3)=8
c, (3x-5).(7-5x)+(5x+2).(3x+2)-2=0
d, x.(x+1).(x+6)-x3=5x
a. (3x - 1).(2x + 7) - (x + 1).(6x - 5) = 16
<=> 6x^2 + 19x - 7 - (6x^2 + x - 5) = 16
<=> 18x - 2 = 16
<=> 18x = 18
<=> x = 1
b. (10x + 9).x - (5x - 1).(2x + 3) = 8
<=> 10x^2 + 9x - (10x^2 + 13x - 3) = 8
<=> -4x + 3 = 8
<=> -4x = 5
<=> x = -5/4
c. (3x - 5).(7 - 5x) + (5x + 2).(3x - 2) - 2 = 0
<=> -15x^2 + 46x - 35 + 15x^2 - 4x - 4 - 2 = 0
<=> 42x - 41 = 0
<=> x = 41/42
Tìm x biết :2x+3/5x+2 = 4x+5/10x+2
2x+3/5x+2 = 4x+5/10x+2
<=> (2x+3)(10x+2)=(5x+2)(4x+5)
<=>2x(10x+2)+3(10x+2)= 5x(4x+5)+2(4x+5)
<=> 20x^2+4x+20x+6 = 20x^2+25x+9x+10
<=> 20x^2+4x+20x+6 - (20x^2+25x+9x+10)=0 => 20x^2+24x+6-(20x^2+34x+10)=0
<=> -10x-4=0
<=>-10x=4
<=> x= -4/10
2x+3/5x+2=4x+5/10x+2
=> (2x+3)(10x+2)=(5x+2)(4x+5)
=> 20x^2+4x+30x+6=10x^2+25x+8x+10 ( Vì cả hai vế đều có 10x^2 nên ta xóa đi )
=> 34x+6=33x+10
=> 34x-33x=-6+10
=> x=4
2x+3/5x+2=4x+5/10x+2.Tìm x
\(\frac{2x+3}{5x+2}=\frac{4x+5}{10x+2}\Leftrightarrow\left(2x+3\right)\left(10x+2\right)=\left(4x+5\right)\left(5x+2\right)\Leftrightarrow20x^2+34x+6=20x^2+33x+10\Leftrightarrow x=4\)
Tìm x biết: 2x+3/5x+2=4x+5/10x+2
Tìm x biết :2x+3/5x+2 = 4x+5/10x+2